Adam, Satan, and the King of Tyre: the interpretation of Ezekiel 28:11-19 in late antiquity - Patmore, Hector M. ca. 20./21. Jh. (Jewish and Christian perspectives series, 2012)
The oracle against the King of Tyre, found in Ezekiel 28.12-19, is a difficult text that inspired diverse interpretations in Late Antiquity. This book examines those interpretations and seeks to understand their origins and development